Shedding light on the tympanic membrane: a brief history of the description and understanding of its anatomy. Issue 2 (25th February 2022) - Baudouin, R; Denoyelle, F; Simon, F
Abstract: Objective: For centuries, the tympanum has remained the only visible structure of the organ of hearing. This study aimed to trace the understanding of the tympanic membrane from antiquity to the early twentieth century. Methods: A review was conducted of primary and secondary historical and scientific literature describing the tympanic membrane anatomy. Results: Although ancient polymaths sensed that sounds were vibrations that could spread in the air and be perceived by the hearing organ, there were numerous misconceptions about the tympanum until human dissections performed during the Renaissance. The tympanum was correctly described only centuries later when technological advances enabled otologists to understand it as a fundamental part of the hearing organ. Conclusion: The tympanic membrane history reflects key stages in medical knowledge; limited for centuries, a great technological leap was possible in the nineteenth century, contributing to the emergence of otologists and laying the foundations of modern otology.